Validation of the Structured Interview for the Assessment of Expressed Emotion (E5) in a Sample of Adolescents and Young Adults From the General Population - Muela-Martinez, Jose-Antonio; Espinosa-Fernandez, Lourdes; Garcia-Lopez, Luis-Joaquin; Martin-Puga, Maria-Eva (Frontiers in Psychology, 2021)
Expressed emotion (EE) is an index of signiﬁcant others’ attitudes, feelings, and behaviour toward an identiﬁed patient. EE was originally conceptualized as a dichotomous summary index. Thus, a family member is rated low or high on how much criticism, hostility, and emotional overinvolvement (EOI) s/he expresses toward an identiﬁed patient. However, the lack of brief, valid measures is a drawback to assess EE. To cover this gap, the E5 was designed. The objective of this study is to provide psychometric properties of a recent measured in adolescents to be used to tap perceived high levels of EE. The sample was composed by 2905 adolescents aged from 11-19 years; 57% girls). Results demonstrate good factor structure, reliability, construct validity and invariance across gender and age revealed a good fit. As a result, E5 is a brief, valid and reliable measure for assessing expressed emotion in parents of adolescent children.